PENINGKATAN KINERJA SDM APARATUR MELALUI DIKLAT DAN PROMOSI JABATAN YANG BERIMPLIKASI TERHADAP PELAYANAN PUBLIK PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN MALANG - Abdul Malik (Lembaga Administrasi Negara, 2018)
This research is explanative causality research which aims to analyze the influence of education and training variables (Diklat) as well as promotion of position on the performance of employees that have implications for the service to the community. The study was conducted at the Investment and Integrated Service Department of Satu Pintu Malang Regency, the sampling was conducted by census, where the entire population was sampled, that is 70 respondents. Data analysis calculated by quantitative approach using inferential statistic with multiple linear regression to answer the research objective by knowing the influence between independent variable to dependent variable. The results of this study indicate that there is posistif influence and significant variables Diklat and promotion positions on employee performance, there is a positive and significant influence Training and promotion of positions to public services, and there is a significant influence also between employee performance variables to community services . This means that, the service of State Civil Servant (ASN) to the community can be improved by improving the performance of the apparatus. This performance improvement can be implemented by providing education and training as well as promotion of positions to employees who deserve to be promoted.Keywords: HR Performance, Training, Promotion, Public service